EFFECT OF PHOTO INITIATION TREATMENTS ON FLOWERING, POLLEN VIABILITY AND SEED GERMINABILITY OF FOUR SUGARCANE CLONES - Abu-Ellail, Farrag F.B.; Mohamed, Bazeed D (Journal of Sugarcane Research, 2020)
The research reported here, was conducted during 2016 and 2017 at the breeding station of Sugar Crops Research Institute, Agriculture Research Center (ARC), Giza, Egypt (30° 0’ N latitude, 31° 12’ E longitude),to examine the response of three sugarcane clones (Co1129, IK76-99, and NCo339) and the commercial cultivar GT54-9, to four photo-initiation treatments of constant 12.5-h days of 15-, 21-, 30-, and 60-days length followed by a declination of 30 s/d to 11 h 30 min.. The four sugarcane clones varied considerably in their initiation response. None showed any flowering response to the 15-day treatment. However, they revealed differential responses regarding their flowering dates for the 21-, 30-, and 60-day photo-initiation treatments. Their flowering dates were delayed by increasing the number of initiation cycles. The cultivar GT54-9 responded only to the 21-day treatment. Co1129 responded best to the 30-day treatment with 50% flowering but produced no flowers in the 21-day treatment. IK76-99 and NCo339, with 50% flowering, responded best to the 30-day treatment. Increasing the length of the inductive cycle reduced pollen viability. This resulted in decreased seed germinability and germination speed. We suggest all germplasm be screened under different photo-initiation cycles to define and select parents for sugarcane breeding program so all cross combinations can be made among synchronized flowering parents.